TELAAH THEORY OF POINTLESS PUNISHMENT TERHADAP PSIKOPAT SEBAGAI PELAKU TINDAK PIDANA DALAM PUTUSAN MAHKAMAH AGUNG NO. 14444 K/ PID/ 2009 - Mardian Putra Frans (UNIB Press, 2022)
This paper discusses the application of the theory of pointless punishment related to psychopaths as criminals using a conceptual approach. The paper argues that psychopaths are part of a mental illness that cannot be criminally responsible as intended in Article 44 paragraph (2) of the Criminal Code. Furthermore, this paper willw explain one of the reasons for the theory of criminal eradication which strengthens the previous opinion that psychopaths cannot be convicted, namely the theory of pointless punishment. Because this theory emphasizes the benefits of giving punishment to those who deserve punishment, psychopaths who are categorized as other mental illnesses cannot be held accountable because they do not get benefits if they receive punishment or punishment. Keywords: Psychopaths; Accountability; Punishment.